Eating behaviors, adherence, and acceptance of a healthy and sustainable diet in Zamorano - Enriquez M., Jean P. (Zamorano: Escuela Agrícola Panamericana, 2021, 2021)
Sustainable diets arise as a challenge to the nutritional problems of public health, and the lack of sustainability of food systems, requiring the transformation and the eating behaviors of university youth towards sustainable consumption and production. The objectives of the research were to determine student´s adherence to a healthy and sustainable diet (HSD), to establish the influence of motivations on food choices and behaviors before and after educational interventions, and to sensorially evaluate the acceptance of dishes prepared with local products. A prospective longitudinal study was conducted with two groups, one of whom received eight educational interventions, four face-to-face and four online, seeking to make them aware of the benefits of DSS, and one group had no interventions. The target population was Zamorano University first-year undergraduate students from 16 countries. The group's eating habits were improved with interventions, going from unhealthy to moderately healthy habits. There were no improvements in relation to adherence to the DSS in any group. The students presented a good acceptance of the menus with little waste on the tray.